Profit shifting by EU banks: evidence from country-by-country reporting - Serena Fatica; Gregori Wildmer (Publications Office of the European Union, 2018)
We investigate profit shifting by the largest and systemically relevant European multinational banks using new data made available through country-by-country reporting for the financial years 2014-2016. We capture tax incentives for income shifting using a multilateral tax differential between the local tax rate and the tax rates in the other countries where the bank has operations. We find that profits - particularly those recorded in tax havens - are negatively affected by corporate taxation. Moreover, the bulk of income shifting seems to take place among subsidiaries, as foreign-to-foreign tax differences matter significantly more that home-to-foreign differentials. Simulation results suggest that the amount of shifted profits in tax havens is about 38% of true profits. The ratio between shifted and true profits drops to about 7% when selected non havens are considered.
Keywords: G21; G28; H26; H87; 330; banks; tax havens; regulation; tax avoidance; transparency